Synthesis of Calcium Phosphate from Boiler Egg Shells as Raw Material for Hydroxyapatite - Luluk Edahwati; Sutiyono; Rahmaniar Naulita Hutagalung; Siti Robiatuz Zahrotun Nukhuf (Future Science, 2022)
Hydroxyapatite (Ca10(PO4)6(OH)2) is one of the biomaterials that can be used for replacement bones for survivors of fractures that can be caused by accidents or natural disasters. Hydroxyapatite biomaterials are now a necessity, but the high price of imported hydroxyapatites has resulted in difficulties in obtaining them. The purpose of this study is to synthesize calcium phosphate from the eggshells of purebred chickens so that they can be used as raw materials for making hydroxyapatite. The stages in the manufacture of calcium phosphate are calcination as a pretreatment process of purebred chicken egg shells which is continued with the synthesis process. The research variables used are variations in phosphoric acid concentrations and also pH variations. The results presented were regarding calcium content through XRF analysis, diffraction patterns from calcium phosphate through XRD analysis, and morphology of calcium phosphate through SEM analysis. From the results of the analysis, it can be used as a reference for the characteristics of calcium phosphate which will be used as a raw material for making hydroxyapatite.